Studies on the function of heparan sulfate in the C. elegans germ line - Cunha, Dayse Caroline Severiano da [UNIFESP] (2016)
Germline development is a process common to all multicellular organisms and requires tight control of proliferation and stem cell maintenance. The Caenorhabditis elegans hermaphrodite germline was used in this thesis as a model to study stem cells and cellular proliferation, as well as germ cell fate specification and maintenance. In C. elegans, each germ cell is surrounded by a thickened extracellular matrix, which is comprised of a variety of macromolecules including highly modified heparan sulfate (HS). The HS chains are covalently linked to a core protein to form proteoglycans (PGs). HS chains are modified by heparan sulfate modifying enzymes (HSME). Single orthologs of all known HS-modifying enzymes are found in the C. elegans genome: hst-1/NDST, hst-2/HS2st, hse-5/GLCE, hst- 6/HS6st and two for 3-O-sulfotransferase, hst-3.1 and hst-3.2. Heparan sulfates display peculiar structural variability, which play specific roles in a diversity of cellular interactions. Yet, the understanding of the function of HS in stem cell biology in vivo remains poorly understood. In this thesis, genetic analyses of hermaphrodite germline showed that heparan sulfate is required for germline proliferation. Modifications in the HS chain by hst-2/HS2st restricts germ cell proliferation activity whereas other modifications such as, hst-1/NDST can promote mitotic activity of germ cells. On the other hand, some proteoglycans (SDN-1/syndecan, LON- 2/glypican and UNC-52/perlecan), are required for germ cell proliferation and to prevent premature entry into meiosis. Thus, these genes could be required for stem cell maintenance. However, unc-52/perlecan mutants display an increase in stem cell corpses, which may affect germline proliferation. Moreover, it was found that distal tip cell (DTC) migration defects do not correlate with changes in germline proliferation. Interestingly, no changes occur during cell cycle progression in young adult mutants of sdn-1/syndecan, lon-2/glypican and hst-2/HS2st. In addition, RNAi has the potential to shed light on the function of a gene in distinct tissues. In this thesis, it is shown that sdn-1/syndecan and lon-2/glypican are acting in the somatic gonad that surrounds the germ cells, whereas hst-2/HS2st and hst-6/HS6st act in the germline, indicating complex interactions between the extracellular matrix of the germline and the somatic gonad during normal germ cell development. In addition, it was found that crucial signaling pathways, such as GLP-1/Notch, DAF-2/IIR and DAF-7/TGF-? are genetically epistatic to hst-2/HS2ST during germline proliferation. Taken together, the results demonstrate that modification patterns in the HS chain are required for proper homeostasis of germline stem cells in the C. elegans germline.